You shall not pass! A Chromatin barrier story in plants - Velay, Florent; Méteignier, Louis-Valentin; Laloi, Christophe (Frontiers in Plant Science, 2022)
As in other eukaryotes, the plant genome is functionally organized in two mutually exclusive chromatin fractions, a gene-rich and transcriptionally active euchromatin, and a gene-poor, repeat-rich and transcriptionally silent heterochromatin. In Drosophila and humans, the molecular mechanisms by which euchromatin is preserved from heterochromatin spreading have been extensively studied, leading to the identification of insulator DNA elements and associated chromatin factors (insulator proteins), which form boundaries between chromatin domains with antagonistic features. In contrast, the identity of factors assuring such a barrier function remains largely elusive in plants. Nevertheless, several genomic elements and associated protein factors have recently been shown to regulate the spreading of chromatin marks across their natural boundaries in plants. In this minireview, we focus on recent findings that describe the spreading of chromatin and propose avenues to improve the understanding of how plant chromatin architecture and transitions between different chromatin domains are defined.